Gynecologists are afraid of prescribing hormone replacement to endometrial/ovarian cancer survivors despite national guidelines—a survey in Sweden - Sandra Halldorsdottir; Hanna Dahlstrand; Karin Stålberg (Upsala Journal of Medical Sciences, 2018)
Background: Prolonged survival in ovarian and endometrial cancer patients increases the importance of paying attention to quality of life. Hormone replacement therapy (HRT) after gynecologic cancer has been controversial. With this survey, we sought to describe Swedish gynecologists’ and gynecologic oncologists’ attitudes towards prescribing HRT to these cancer survivors and see if prescribing practice is consistent with the available evidence and national guidelines. Material and methods: A web-based survey containing three hypothetical cases with a total of 15 questions was distributed to gynecologists and gynecologic oncologists in Sweden. Respondents were asked about their HRT prescription practices in endometrial/ovarian cancer patients with moderate to severe menopausal symptoms. Results: In total 262 gynecologists and 24 gynecologic oncologists answered the survey. In the low-risk endometrial cancer case a majority of the gynecologists (55%) and gynecologic oncologists (66.7%) would prescribe local estrogen. A total of 30% of the gynecologists would prescribe estrogen replacement therapy (ERT) in the high-risk endometrial cancer case compared to 58.3% of the gynecologic oncologists. The gynecologic oncologists felt more comfortable treating patients with endometrial cancer than did gynecologists, and the gynecologists were more likely to read the national guidelines. In the ovarian cancer case, 63.7% of the gynecologists would prescribe HRT compared to 92% of the gynecologic oncologists. Conclusion: Swedish gynecologic oncologists have a more favorable attitude towards HRT for endometrial/ovarian cancer patients and feel more comfortable treating their patients than do gynecologists. This study illustrates a need for education in these matters in order not to withhold HRT from women due to doctors’ sometimes unjustified anxiety.